2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626065
|View full text |Cite
|
Sign up to set email alerts
|

Complexity analysis of the uterine electromyography

Abstract: In respect to the main goal of our ongoing work for predicting preterm birth, we analyze in this paper the complexity of the uterine electromyography (EMG) by using the sample entropy (SampEn) algorithm. By considering recent methodological developments, we measure the SampEn over multiple scales using the wavelet packet decomposition method. The results obtained from the analyzed data indicate that SampEn decreases along pregnancy. Furthermore, we demonstrate that the computed SampEn parameter may discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Previous studies reported that the irregularity of EHG evaluated by SampEn gradually decreases during pregnancy [ 11 ]. Other evidence indicates that the values of SampEn are higher during the latent phase in comparison to the active phase of labor, indicating that the irregularity of the uterine EHG signal is reduced in the active phase of labor [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that the irregularity of EHG evaluated by SampEn gradually decreases during pregnancy [ 11 ]. Other evidence indicates that the values of SampEn are higher during the latent phase in comparison to the active phase of labor, indicating that the irregularity of the uterine EHG signal is reduced in the active phase of labor [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies indicate that spontaneous uterine contractions contain nonlinear features [ 9 ]. Additionally, changes in the dynamics of EHG between term low-risk parturient and non-parturient women have rarely been explored by using diverse entropy approaches [ 7 , 10 , 11 ]. Authors highlight the necessity of finding suitable measures that characterize electrohysterographic time series generated by the uterine activity during parturition [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, other sophisticated uterine EMG parameters not considered in this study (e.g. propagation velocity, fractal dimension, complexity [42],. .…”
Section: Discussionmentioning
confidence: 99%
“…The real uterine EMG signals used in this study were recorded on 32 women: 22 women were recorded during pregnancy (33 -41 week of gestation, WG), 7 during labor (37 -42 WG) and 3 during both pregnancy and labor (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The mean and standard deviations of the gestational ages for pregnancy and labor were 34.14 ± 3.94 and 39.6 ± 1.75 weeks, respectively.…”
Section: Database Descriptionmentioning
confidence: 99%
“…Therefore, nonlinear methods including time reversibility, sample entropy, Lyapunov exponents and delay vector variance [11], nonlinear interdependencies [10], and multifractal analysis [12, 13] are useful for EHG analysis. Some advanced algorithms including the Hilbert transform, cross-correlation [14], correlation coefficient H 2 [5], mutual correlation dimension, cross-approximate entropy [15], and dynamic cumulative sum [16] have also been proposed for UC detection. Besides, classifiers including the support vector machine [17], random forest, and artificial neural network [7] have been developed for automatic UC detection using TOCO, cardiotocogram [18], and EHG signals.…”
Section: Introductionmentioning
confidence: 99%